2013
DOI: 10.1007/s10856-013-5116-x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cu2+ from a copper-filled TiO2 coating in a rabbit model for total knee arthroplasty

Abstract: The aim of this study was the investigation of a copper-filled TiO2 coating, that in vitro showed good antibacterial properties combined with good tissue tolerance in an animal model. To better understand the antibacterial mechanism of the bioactive coating the release of copper (Cu) ions over time was monitored to be able to detect possible threats as well as possible fields of application. 30 New Zealand White rabbits were divided into two groups with 15 animals per group. In group 1 (control group) Ti6Al4 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…These coatings (4xCu-TiO 2 ) caused a decrease in the number of adhering bacteria (more than 6 log) and a reduction in bacterial growth in the surrounding medium, suggesting a release of Cu ions (180). The same authors confirmed these results in further studies both in vitro (181) and in animal models (182). Hang et al (183) fabricated Cu-TiO 2 nanotube coatings with different Cu contents.…”
Section: •-mentioning
confidence: 81%
“…These coatings (4xCu-TiO 2 ) caused a decrease in the number of adhering bacteria (more than 6 log) and a reduction in bacterial growth in the surrounding medium, suggesting a release of Cu ions (180). The same authors confirmed these results in further studies both in vitro (181) and in animal models (182). Hang et al (183) fabricated Cu-TiO 2 nanotube coatings with different Cu contents.…”
Section: •-mentioning
confidence: 81%
“…Such behavior could represent a good model for bacteremia without ongoing sepsis. Several antibacterial coatings (antibiotics, antiseptics, metal ions, non‐metal ions, or organic molecules) of implants in orthopedics have been developed, and the ability of such implants to minimize bacterial adhesion or inhibit biofilm formation has been investigated. However, we believe that to date, the antibacterial activity against hematogenous infection has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives to minimize bacterial colonization at the time of insertion have been studied in the past with slow permeation in the clinical setting [1,39,48]. Several preclinical and clinical studies support the use of copper alloy touch surfaces to reduce the burden of bacteria in healthcare settings [10,11,33], but few studies support the use of copper implants to reduce periprosthetic infections [6,18,27,41]. The ideal antibacterial coating should be biocompatible, thin, dense, and firm with precise decay of the active material.…”
Section: Discussionmentioning
confidence: 99%